Affordable oral health care: dental biofilm disruption using chloroplast made enzymes with chewing gum delivery. Issue 10 (22nd June 2021) - Singh, Rahul; Ren, Zhi; Shi, Yao; Lin, Shina; Kwon, Kwang‐Chul; Balamurugan, Shanmugaraj; Rai, Vineeta; Mante, Francis; Koo, Hyun; Daniell, Henry
Summary: Current approaches for oral health care rely on procedures that are unaffordable to impoverished populations, whereas aerosolized droplets in the dental clinic and poor oral hygiene may contribute to spread of several infectious diseases including COVID‐19, requiring new solutions for dental biofilm/plaque treatment at home. Plant cells have been used to produce monoclonal antibodies or antimicrobial peptides for topical applications to decrease colonization of pathogenic microbes on dental surface. Therefore, we investigated an affordable method for dental biofilm disruption by expressing lipase, dextranase or mutanase in plant cells via the chloroplast genome. Antibiotic resistance gene used to engineer foreign genes into the chloroplast genome were subsequently removed using direct repeats flanking the aadA gene and enzymes were successfully expressed in marker‐free lettuce transplastomic lines. Equivalent enzyme units of plant‐derived lipase performed better than purified commercial enzymes against biofilms, specifically targeting fungal hyphae formation. Combination of lipase with dextranase and mutanase suppressed biofilm development by degrading the biofilm matrix, with concomitant reduction of bacterial and fungal accumulation. In chewing gum tablets formulated with freeze‐dried plant cells, expressed protein was stable up to 3 years at ambient temperature and was efficiently released in a time‐dependent manner using a mechanical chewing simulator device. Development of edible plant cells expressing enzymes eliminates the need for purification and cold‐chain transportation, providing a potential translatable therapeutic approach. Biofilm disruption through plant enzymes and chewing gum‐based delivery offers an effective and affordable dental biofilm control at home particularly for populations with minimal oral care access.